DOCOMOMO News - Various Authors (Docomomo Journal, 2022)
News regarding the Villa Schocken in danger, Founding of DOCOMOMO RI, Brazilian DOCOMOMO Working Party report, DOCOMOMO Korea Symposium, Reports from DOCOMOMO Greece, news from the ISC/U+L.